Critical mass - Paretsky, Sara (Paretsky, Sara. V.I. Warshawski novel., 2013)
" New York Times-bestselling author Sara Paretsky's brilliant protagonist V.I. Warshawski returns in another hard-hitting entry, combining razor-sharp plotting and compelling characters with a heady mix of timely political and social themes. V.I. Warshawski's closest friend in Chicago is the Viennese-born doctor Lotty Herschel, who lost most of her family in the Holocaust. Lotty escaped to London in 1939 on the Kindertransport with a childhood playmate, Kitty Saginor Binder. When Kitty's daughter finds her life is in danger, she calls Lotty, who, in turn, summons V.I. to help. The daughter's troubles turn out to be just the tip of an iceberg of lies, secrets, and silence, whose origins go back to the mad competition among America, Germany, Japan and England to develop the first atomic bomb. The secrets are old, but the people who continue to guard them today will not let go of them without a fight. "--